Jumlah konsumsi dan metode memasak ikan terhadap kejadian dislipidemia - Farida Nailufar; Martalena Br Purba; Emy Huriyati (Jurnal Gizi Klinik Indonesia, 2013)
Background: Some studies state that fish consumption of at least 200-400 g/week can reduce the risk of coronary heart disease. Omega 3 polyunsaturated fatty acids in fish have cardioprotective effects. However, the cardiac effect of fish consumption are not primarily related to the amount of fish consumed but also its cooking method. The cooking method (eg, frying) may alter the fatty acid content of a fish meal by absorbing fatty acids from cooking oils and adding trans fatty acids. Non-fried fish consumption (eg, boiled/steamed) was associated with lower risk of coronary heart disease but fried fish was not.Objective: To identify the quantity of fish consumed and the cooking method with the incidence of dyslipidemia.Method: The study was observational with case control design in patients that checked themselves at Prodia laboratory of Samarinda. Respondents consisted of 152 patients, comprising 76 cases and 76 control. Cases were patients with dyslipidemia and control were those without dyslipidemia matched according to gender and age. Analysis used Chi-Square statistical test at confidence interval 95%.Results: There was significant difference in average of fish consumed between case and control group (164.86±63.61 g vs 218.55±62.21 g; p<0.05). There was also significant difference (p<0.05) between case and control group in variables of body mass index (24.53±2.4 kg/m2 vs 23.26±1.6 kg/m2); intake of saturated fatty acids (SFA) (34.58±5.82 g vs 28.27±5.4 g); simple carbohydrate (63.86±13.67 g vs 49.35±11.81 g); fruit and vegetable (42.61±20.17 g vs 53.48±23.47 g); and waist circumference (88.88±9.08 cm vs 86.21±7.8 cm). In the final multivariate analysis, quantity of fish consumed has no influences with dyslipidemia (p>0,05), but the influence is in the cooking method process (OR=10,84; p<0,05).Conclusion: There was no influence between quantity of fish consumption. Risk for the prevalence of dyslipidemia was 10,84 times greater in the subject who the cooking method does not suitable the recommendation.